Review with Analytical-Numerical Comparison of Contact Force Models for Slotted Joints in Machines - Matteo Autiero; Mattia Cera; Marco Cirelli; Ettore Pennestrì; Pier Paolo Valentini (Machines, 2022)
The pin-in-the-slot joint is a common element in machines, and the dynamics of joints with clearances is an actively investigated topic. Important applications of such a joint can be found in Geneva mechanisms, robotized gear selectors, centrifugal vibration absorbers (CPVA) and other important mechanical devices. The paper will review the main analytical steps required to obtain the equations characterizing the different force contact models. Furthermore, a numerical test bench where such models are introduced for modeling the clearances between the pin and slot is proposed. In this regard, the present study will offer a comparison and discussion of the numerical results obtained with the different force contact models herein reviewed.